Program Pengembangan Pariwisata Air Terjun Banyu Nibo dan Potensi Desa Rejosari Kabupaten Gunungkidul Daerah Istimewa Yogyakarta - Susilawati, Marietta (Jurnal Atma Inovasia, 2023)
Community Service Program is a form of academic activity from the campus through work programs that focus on village potential and the development of this potential to help improve the economic, tourism, educational, and socio-cultural sectors that can impact the welfare of the entire village community. The methodologies used include problem identification, literature study, data collection, data processing, output generation, evaluation, and drawing conclusions. The work program is expected to provide results in developing and promoting the Banyu Nibo waterfall tourist attraction, which the village community can use as a tourism characteristic of Rejosari Village.